An induced detenninate mutant in fenugreek (Trigonella foenum-graecum L.) - Singh, A K Chaudhary, V V (Journal of Spices and Aromatic Crops, 2001)
A determinate mutant was isolated from a population of 400 plants of fenugreek (Trigonella foenum-graecum L.) in the M2 generation raised from 200 seeds of Rmt 1 (indeterminate variety) treated with ethyl methane sulphonate (EMS) 0.10% for 4 h. Random samples from all M2 populations (except the mutant) were advanced to M3 generation. The appearance of one determinate type in a sample of 798 plants indicated that the trait is monogenic. This mutant was grown along with Rmt 1 and UM 305 (spontaneous mutant for similar growth habit). There were significant differences among genotypes for plant height, number of pods per plant, seed yield per plant and aphid infestation. The study indicated that the performance of the mutant could be brought on par with the checks following selection for desired economic traits.